2016
DOI: 10.1016/j.ejogrb.2016.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Maternal cardiac deceleration capacity: a novel insight into maternal autonomic function in pregnancies complicated by hypertensive disorders and intrauterine growth restriction

Abstract: Women with pregnancy complicated by severe placental failure, such as HDP-IUGR and severe IUGR, show significant autonomic alterations, as indicated by elevated cardiac DC. On the contrary, pregnancy complications such as HDP-AGAf and mild IUGR show no impact on maternal autonomic balance. We present a new approach to explore maternal autonomic cardiovascular regulation that might reflect the severity of placental vascular insufficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…To this end, we hypothesize that the reduced autonomic responsiveness (which is reflected in our PRSA analyses as well as the known reduced neurocardiovascular transduction in pregnancy) is a mechanism by which the mother is protected against her autonomic state. This theory is further reflected in findings from Casati et al (2016), who observed increased autonomic responsiveness in women with pregnancy complications (such as hypertensive disorders of pregnancy) when compared to healthy pregnant controls. Subsequently, we believe PRSA analysis may be particularly useful in assessing maternal health via mHRV.…”
Section: Discussionmentioning
confidence: 92%
“…To this end, we hypothesize that the reduced autonomic responsiveness (which is reflected in our PRSA analyses as well as the known reduced neurocardiovascular transduction in pregnancy) is a mechanism by which the mother is protected against her autonomic state. This theory is further reflected in findings from Casati et al (2016), who observed increased autonomic responsiveness in women with pregnancy complications (such as hypertensive disorders of pregnancy) when compared to healthy pregnant controls. Subsequently, we believe PRSA analysis may be particularly useful in assessing maternal health via mHRV.…”
Section: Discussionmentioning
confidence: 92%
“…Therefore, acquiring measurements without the influence of such medications is not trivial. Some researchers avoid this by performing short measurements before corticosteroids are administered [9,40], while others mention these obstetric medications as potential confounders in their limitations [11,12]. Others still make no mention of corticosteroids, even though according to standard treatment protocols it is likely that their study groups would have been administered these medications [13,[41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…However, investigations into the mHRV of women with complicated pregnancies have been hindered by the routine administration of obstetric medications, such as tocolytics, beta-blockers, and corticosteroids, which are administered to women upon the diagnosis of complications. As the effect of these medications on mHRV is largely unknown, it is uncertain to which degree changes in HRV in this population reflect autonomic dysregulation associated with pregnancy complications, as opposed to merely reflecting the confounding effect of these medications [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…However, the accompanying effect sizes are small and the dampening in HR responsiveness is not comparable to that seen in diseased states ( Bauer et al, 2006b ). Furthermore, the two other studies that have calculated PRSA to study maternal HRV found no significant correlations with GA ( Casati et al, 2016 ; Carpenter), although only DC was studied and assessing its correlation with GA was not the primary aim of these studies.…”
Section: Discussionmentioning
confidence: 99%
“…PRSA-based features not only independently predict mortality in cardiac disease ( Bauer et al, 2006b ; Eick et al, 2015 ) but are also sensitive to aging and fitness levels ( Campana et al, 2010 ). This method is increasingly being employed to assess fetal health ( Graatsma et al, 2012 ; Georgieva et al, 2014 ) but has rarely been used to assess maternal autonomic modulation ( Tejera et al, 2012 ; Casati et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%